DETERMINATION OF QUALITY AND QUANTITY INDICATORS OF «AYRITOSH» FOOD SUPPLEMENT (Scientific journal of the Fergana State University, 2024)
In this article, we will discuss «AYRITOSH», a herbal supplement that dissolves excess salt and stones in the gall bladder, liver, spleen, kidney, and other organs, improves immunity, and has many other healing properties. the results of some quality indicators were presented. the results of some quality indicators were presented. According to the requirements of XI DF, it was determined that the moisture content of «AYRITOSH» medicinal food additive is 5.59%, and the ash content is 4.5%, and the amount of substance insoluble in 10% hydrochloric acid is 1.01%. It has been proved on the basis of experiments that these indicators are in full compliance with the requirements of the XI DF.